The Brazilian Carbon Capture and Storage (CCS) institutional framework: the new carbon market business in an energy transition economy. - Araújo, Israel Lacerda de (2021)
This thesis proposes an institutional model for the development of Carbon Capture and Storage (CCS) under the legal and regulatory frameworks in Brazil. This model allows agents using best practices and take advantages of the Brazilian potential in the carbon markets, national and international, based on the CCS technology and under the long-term perspectives. Through a comparative study, the CCS best practices and the implementing policies have been analysed, especially those in the USA, Canada, Norway, the United Kingdom, the Netherlands, the UAE, Saudi Arabia and China. For them, the instruments pursued tried to solve market failures linked to climate change and political specificities, and to incentivize the CCS deployment. The study analysed also how to incentivize the CCS technology through fiscal, regulatory and public policy instruments, considering the premise of reduced impact of costs for consumers (and citizens), the need of dealing with political uncertainties, the long-term responsibilities, and the market failures that inertially work in favour of rent seeking behaviour, inter- and intra-sectorial oligopolies in which, in a broad sense, would tend to verticalize business and reduce the engagement of other than the oil industry and bioenergy agents. In Brazil, the current incentives for the CCS adjacent sectors indicate a potential deployment to the CCS clusters using the production of biofuels, electricity, and particularly for hydrocarbon exploitation under the CO2-EOR. The institutional perception allows us to conclude that the legal, regulatory, normative and framework for the CCS business should be built considering the empowerment of a few regulatory and political authorities (RCA and PCA, respectively), the existing institutions, promoting changes incrementally to maintain the current engagement of prior sectors with high CO2-GHG emissions according to business as usual. In addition, issues related to the complexity of costs transfer to final consumers should be considered, under the risk of compromising public perception and political veto. The model to be implemented in the Brazilian legal framework will need to present solutions to virtually reduce political and long-term risks, cross-chains risks horizontally and vertically.